POLEMIK PERNIKAHAN ADAT PELANGKAH DESA SRIMARTANI KECAMATAN PIYUNGAN KABUPATEN BANTUL - Ngainurrofik Ngainurrofik; Moh. Durrul Ainun Nafis; Rizky Maulidah Khasanah (LPPM IAI IBRAHIMY GENTENG BANYUWANGI, 2022)
The practice of Pelangkah customary marriage is a serious study in Islamic studies because it is related to customs and sharia, while ÃƒÂ¢Ã¢â€šÂ¬Ã…â€œPelangkahÃƒÂ¢Ã¢â€šÂ¬Ã‚Â is defined as the giving of goods or money in a family when a younger brother precedes an older brother in terms of marriage. This study addresses two issues: the practice of marriage and the leaders' attitudes toward the Pelangkah custom. This is a study based on data gathered from interviews with traditional actors, religious leaders, and local community leaders. This study is a descriptive analytic study that includes data collection methods, data compilation, and final data analysis. The study's findings show that first, the Pelangkah customary marriage practice is based on two perspectives, and that the perspective of the Pelangkah customary minority is irrelevant in this modern era. The opposing viewpoint, on the other hand, accepts the Pelangkah custom as a form of respect for older relatives through the exchange of goods or money. Second, religious leaders and local community leaders believe that the Pelangkah custom does not violate syara' law and is classified as al-'urf al-khÃƒÆ’Ã‚Â¢sh because it is only practiced in Srimartani Village, Piyungan District, Bantul Regency.